Fiscal Space for Health Care: Modern Approaches to Formation and Diagnostics - Stepanova, O. V. (Statistics of Ukraine, 2018)
In the article an analytical review of theoretical approaches to the definition of the fiscal space is conducted. The peculiarities of the interpretation of the essence of the fiscal space for financing the health care system in the contemporary economic researches are explored. It has been determined that fiscal space for the health care system is in fact one of the conceptual approaches for studying the optimal parameters and proportions of financing of the health care, as well as determining the potential reserves for its increase. Based on the study of foreign experience, it is substantiated that the main factors of fiscal space capacity building for health are: macroeconomic context; the need to ensure the fiscal sustainability in the medium and long-term; peculiarities of models of collection of financial resources, accumulation of financial resources and distribution of financing for the medical services; the priority of public financing of the health care system; the possibility of increasing public financing of health care and the introduction of additional mechanisms for increasing financial resources for health care. It is shown that the state can create fiscal space for financing health care system on the basis of three components: financial resources collection system; systems of accumulation of financial resources; system of distribution of financial resources for the provision of medical services to the population. The analysis of the structure and volume of public health financing in OECD countries has been conducted. The results of the analysis allow us to notice the existence of various proportions of financing the health care, even in the context of the use of identical dominant financing mechanisms. It is determined that among the studied countries the share of countries with the budget financing mechanism of health care is the largest. It is shown that financing of the health care system in Ukraine is considerably smaller than in the OECD countries. The necessity of diagnostics the potential of fiscal space for the health care in Ukraine is substantiated. The indicators of diagnostics of fiscal space for the health care system are systematized in four projections, in particular: indicators of macroeconomic potential; indicators of fiscal capacity; indicators of the pressure of changes in health care expenditures on the fiscal sustainability of; indicators of demographic and social pressure. The need to diagnostics of the potential for fiscal space for health care should be interconnected with indicators of medium and long-term fiscal sustainability.